The Rectangular Elements for Electric Field Calculation by using Numerical Methods - ปานกลาง, นิติพงศ์ (Frontiers in Engineering Innovation Research, 2006)
This paper presents the application of linear rectangular elements and 12-DOF elements for electric field calculation by using surface charge method. The high voltage engineering problem which is used as a case study in this paper is electric field calculation on a dielectric spherical under the uniform electric field. The result from calculating the electric field on z-axis shows that when using linear rectangular elements. the average error of electric field is equal to 1.61%. while 12-DOF elements can reduce the average error to 0.72% or 55.3% reduction.